Factors Influencing Students Performance in Financial Accounting I - Zurita, Mustafa (2009)
This study was carried out to identify the factors that influence the student performance in Financial Accounting 1. The 67 respondents are comes from Certificate in Business Administration Course in Ungku Omar Polythecnic. The research was conducted by giving out the questionnaire to respondents who have taken the subject. A set of questionnaire was designed to obtain primary data from the respondents about the factors that influence their performance in Financial Accounting 1. The overall findings of the study indicates that students Cumulative Grade Point Average (CGPA) and Prior accounting Knowledge (PAK) were factors influencing students performance in Financial Accounting 1, with CGPA was influence most. In conclusions, some suggestions have been made to enhance the achievement of students in this subject and recommendation for future research has also been included in the final part of the report.